2021
DOI: 10.15252/embr.202052124
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of LncRNA CRNDE in TAM‐derived exosomes is linked with cisplatin resistance in gastric cancer

Abstract: This study explores the role of the long noncoding RNA (LncRNA) CRNDE in cisplatin (CDDP) resistance of gastric cancer (GC) cells. Here, we show that LncRNA CRNDE is upregulated in carcinoma tissues and tumor‐associated macrophages (TAMs) of GC patients. In vitro experiments show that CRNDE is enriched in M2‐polarized macrophage‐derived exosomes (M2‐exo) and is transferred from M2 macrophages to GC cells via exosomes. Silencing CRNDE in M2‐exo reverses the promotional effect of M2‐exo on cell proliferation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 41 publications
(41 reference statements)
1
42
0
Order By: Relevance
“…As previous research works reported, lncRNA SNHG7 has been widely reported in various cancers to promote M2 polarization, therefore enhancing drug resistance ( Zhang et al, 2021 ). Silencing lncRNA CRNDE in M2-exo reverses the promotional effect of M2-exo on cell proliferation in CDDP-treated gastric cancer cells ( Xin et al, 2021 ). Moreover, lnc-TALC could be transmitted to TAMs and promote M2 polarization of the microglia ( Li Z. et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…As previous research works reported, lncRNA SNHG7 has been widely reported in various cancers to promote M2 polarization, therefore enhancing drug resistance ( Zhang et al, 2021 ). Silencing lncRNA CRNDE in M2-exo reverses the promotional effect of M2-exo on cell proliferation in CDDP-treated gastric cancer cells ( Xin et al, 2021 ). Moreover, lnc-TALC could be transmitted to TAMs and promote M2 polarization of the microglia ( Li Z. et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exosomal-derived long noncoding RNA (lncRNA) TMZ-associated lnc RNA in GBM recurrence (lnc-TALC) modulates the glioblastoma (GBM) microenvironment and reduces the sensitivity of GBM to temozolomide chemotherapy, targeting exosomal-lnc-TALC may overcome TMZ resistance in GBM ( Li et al, 2021b ). Lnc RNA colorectal neoplasia differentially expressed (lnc-CRNDE) is highly expressed in tumor-associated macrophages (TAM) of gastric cancer (GC) patients, and CRNDE can be transferred from M2-polarized macrophages to GC cells via exosomal form and further promote GC cell proliferation and inhibit cisplatin resistance in GC cells ( Xin et al, 2021 ).…”
Section: Detection Of Exosomesmentioning
confidence: 99%
“…In in vitro experiments, the expression level of lncRNA CRNDE was overexpressed in M2-polarized macrophage-derived exosomes (M2-exo) and it was encapsulated into exosomes to be transferred from M2 macrophages to GC cells. Studies showed that after GC cells are treated with M2-exo of silenced CRNDE, their cisplatin sensitivity was significantly enhanced ( Xin et al, 2021 ). Collectively, exosomal lncRNA may help clarify the underlying molecular mechanisms of therapeutic resistance in gastrointestinal cancer and provide promising therapeutic strategies.…”
Section: Biological Roles Of Exosomal Lncrnas In Gastrointestinal Cancermentioning
confidence: 99%